Metal contamination and fractionation in sediments from the lower basin of the Vale do Ribeira (SE, Brazil) - Bonnail, Estefania; Buruaem, Lucas M. [UNESP]; Morais, Lucas G. [UNESP]; Abessa, Denis M. S. [UNESP]; Sarmiento, Aguasanta M.; Angel DelValls, T. (Springer, 2017)
The sediment quality of Ribeira de Iguape River is affected by former Pb extraction mining. Some studies affirm the restoration status of the basin, however, mobility of metals and its associated risk is still questioned. This study integrates the metal concentrations in the lower part of the basin with different contamination source to determine the existence of risks associated with the mobile fractions of the geochemical matrix. Despite concentrations of metals were low and the environmental risk factor values were negative, our results indicated that As, Mn, Pb, and V were present in the most labile forms. The multivariate analysis conducted using metal concentrations, environmental risk factor values and speciation suggested that any risk would be associated with the labile fractions of the analyzed elements, especially for Pb. The station from Registro was stressed by Co, Pb and Zn; with Pb under the reactive fraction that could be associated with high mobility and potential bioavailability.
Keywords: Iguape River; Metal monitoring; Environmental risk assessment; Sequential extraction